Hull-shape parametric for minimising wave energy - Wiwin Sulistyawati; Purwo Joko Suranto; Dian Purnamasari (Energy Reports, 2023)
This study presents a hull-ship parametric in reducing drag for minimising wave energy by comparing various numerical methods. The methods are Thin-ship theory, Rankine method, and Computational Fluid Dynamics (CFD). The methods are discussed in detail, with an emphasis on comparing wave and total drag as energy, wave profiles, and contours. The study results show that Rankine method entirely underpredicts the experimental results. Thin-ship theory cannot be adequately examined with a low Froude number, as evidenced by a test on total drag and calculation of wave energy. Although significant deviations exist, the CFD method provides a drag close to the experimental results. The Rankine approach displays a fairly apparent difference between the wave profile’s original hull of series 60 and the optimum parametric hull. Even if the wave’s profile line is identical to the profile from Rankine’s method, Thin-ship theory results do not sufficiently reveal the difference. From the testing results at Fr 0.24–0.32, the parametric optimal hull significantly reduced wave energy as wave drags by roughly 21%, Rankine by 17%, Thin ship theory by 7%, and CFD by 12.1%, respectively. Moreover, the wave contour of the methods illustrates a reasonably straightforward agreement. The outline of the wave at Fr 0.6 and 1.0 indicates that the optimum parametric hull’s wave contour shows that the wave’s spread is shorter, producing a lower drag.